2004
DOI: 10.1128/iai.72.8.4911-4917.2004
|View full text |Cite
|
Sign up to set email alerts
|

Intact Purine Biosynthesis Pathways Are Required for Wild-Type Virulence of Brucella abortus 2308 in the BALB/c Mouse Model

Abstract: Brucella abortus 2308 derivatives with mini-Tn5 insertions in purE, purL, and purD display significant attenuation in the BALB/c mouse model, while isogenic mutants with mini-Tn5 insertions in pheA, trpB, and dagA display little or no attenuation in cultured murine macrophages or mice. These experimental findings confirm the importance of the purine biosynthesis pathways for the survival and replication of the brucellae in host macrophages. In contrast to previous reports, however, these results indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 29 publications
5
43
0
Order By: Relevance
“…2b). The results presented here are consistent with our previous findings (Truong et al, 2014(Truong et al, , 2015 and the work of other investigators (Alcantara et al, 2004;Yang et al, 2010) demonstrating the important roles of purine biosynthesis (purD, purE) and ABC-type WCAs of strain RB51 or B. canis S26 in sera from vaccinated mice. Results are shown as mean¡SD.…”
Section: Discussionsupporting
confidence: 82%
“…2b). The results presented here are consistent with our previous findings (Truong et al, 2014(Truong et al, , 2015 and the work of other investigators (Alcantara et al, 2004;Yang et al, 2010) demonstrating the important roles of purine biosynthesis (purD, purE) and ABC-type WCAs of strain RB51 or B. canis S26 in sera from vaccinated mice. Results are shown as mean¡SD.…”
Section: Discussionsupporting
confidence: 82%
“…It may be suggested that LysR18 is involved in the control of purine catabolism genes. Until now, only the synthesis of purines was shown to be required for the virulence of Brucella in both cellular and murine models (1,11,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to develop live brucellae vaccines have met with varied success. For instance, inactivation of the amino acid biosynthesis pathway genes pheA, trpB, and dagA displayed little or no attenuation in cultured murine macrophages or in mice (1). The mutants of purine biosynthesis pathway genes purL, purD, and purE (1) displayed significant attenuation in BALB/c mice, but live brucellae remained viable after 12 weeks, suggesting that their virulence was not sufficiently attenuated for adoption as a livestock vaccine.…”
Section: Znmentioning
confidence: 99%